2011
DOI: 10.3892/mmr.2011.478
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of in vivo UVB-induced secretion of IL-1α and IL-6 in keratinocytes

Abstract: Abstract. Keratinocytes play an important role in the inflammatory response of the skin. UVB stimulates keratinocytes to secrete several cytokines. To our knowledge, there are no reports that have examined which layer or cell type is responsible for producing these cytokines. Thus, in this study we performed immunohistochemical experiments to determine the potential cells or layers that express interleukin (IL)-1 and IL-6. The results show that the expression of IL-1α and IL-6 was induced 3 and 6 h after irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…A single exposure of human subjects to 3 MED of SSL (290−400 nm; 1.4-5.6 J/m 2 ) also caused a rapid increase in TNF-α level in blister fluid that started at 4 h, peaked at 15 h and was normalized 48 h after exposure. On the other hand, IL-1α and IL-1β level in blister fluid was significantly increased only at 15 h and remained elevated to 72 h after SSL exposure 14 . Similarly Hiromi et al showed a rapid up-regulation of IL-1α expression induced by UVB (275-305 nm; 200 mJ/cm 2 ) in the skin of the Hirosaki hairless rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single exposure of human subjects to 3 MED of SSL (290−400 nm; 1.4-5.6 J/m 2 ) also caused a rapid increase in TNF-α level in blister fluid that started at 4 h, peaked at 15 h and was normalized 48 h after exposure. On the other hand, IL-1α and IL-1β level in blister fluid was significantly increased only at 15 h and remained elevated to 72 h after SSL exposure 14 . Similarly Hiromi et al showed a rapid up-regulation of IL-1α expression induced by UVB (275-305 nm; 200 mJ/cm 2 ) in the skin of the Hirosaki hairless rats.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 was increased 24 h after exposure, peaked at 36 h and was cleared at 72 h after irradiation 26 . In human subjects exposed to 3 MED of SSL (290-400 nm), IL-10 increase in skin was detected at 15 and 24 h after irradiation 14 . Local exposure of human volunteers to SSL (1 and 3 MED) induced a strong increase in IL-10 mRNA level 24 h after exposure 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocytes populate the stratified epidermis, the outer layer of the skin, and perform vital functions in defense, regeneration, wound healing, and homeostasis . Keratinocytes secrete a variety of growth factors and cytokines to regulate proliferation, migration, differentiation, and apoptosis in the epidermis …”
Section: Introductionmentioning
confidence: 99%
“…7 Keratinocytes secrete a variety of growth factors and cytokines to regulate proliferation, migration, differentiation, and apoptosis in the epidermis. [8][9][10] Cell migration proceeds through a series of steps precisely controlled by a cellular signaling network and the establishment of extracellular matrix proteins. 11 Keratinocytes treated with epidermal growth factor (EGF) markedly increase migratory activity through activation of the extracellular signal-regulated kinase pathway.…”
Section: Introductionmentioning
confidence: 99%